2023
DOI: 10.5114/pedm.2023.124266
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical hypothyroidism in children and adolescents as mild dysfunction of the thyroid gland: a single-center study

Abstract: Introduction: Subclinical hypothyroidism (SH) is a biochemical diagnosis made when a serum thyroid-stimulating hormone (TSH) is elevated with circulating thyroid hormone levels within their reference ranges. Aim of the study: Aim of our prospective non-randomized study was to evaluate the course of SH. Material and methods: All patients with suspicion of SH referred to the Endocrinology Outpatient Clinic between 2014 and 2018 were recruited to prospective study. Results: A total of 130 patients with SH were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…Our data also support the findings from other studies, that treatment with levothyroxine does not decrease weight in individuals with obesity and no thyroid disease ( 28 31 ). This could be partially explained by our findings, with higher FT4 levels predisposing weight gainMore complicated is the situation in individuals with obesity and concomitant Hashimoto thyroiditis.…”
Section: Discussionsupporting
confidence: 92%
“…Our data also support the findings from other studies, that treatment with levothyroxine does not decrease weight in individuals with obesity and no thyroid disease ( 28 31 ). This could be partially explained by our findings, with higher FT4 levels predisposing weight gainMore complicated is the situation in individuals with obesity and concomitant Hashimoto thyroiditis.…”
Section: Discussionsupporting
confidence: 92%
“…While its mild form is relatively benign (if not connected to Hashimoto’s thyroiditis) in the pediatric population, it has been shown that isolated elevation of TSH levels may be related to an increased risk of developing or progressing cardiovascular disease and non-alcoholic fatty liver disease (NAFLD) in children and adolescents suffering from obesity [ 109 ]. Furthermore, it has been also demonstrated that overweight and obesity in children carry a risk of progression from subclinical to overt hypothyroidism [ 110 ]. In spite of this, there is limited information regarding the treatment of thyroid disorders co-occurring with obesity in children [ 109 ].…”
Section: Non-metabolic Complications Of Obesity In Childrenmentioning
confidence: 99%
“…It is advisable to reassess thyroid function after losing weight [ 111 ] because previous reports indicate that weight loss might lead to the normalization of TSH levels [ 69 , 108 ]. Treatment of subclinical hypothyroidism with levothyroxine has not been proven to contribute to weight loss or normalization of lipid and thyroid parameters in children dealing with obesity [ 109 , 110 ]. Thus, if there are no clinical and laboratory indications of overt hypothyroidism, levothyroxine treatment is not required in such a group of patients [ 110 ].…”
Section: Non-metabolic Complications Of Obesity In Childrenmentioning
confidence: 99%
See 1 more Smart Citation